Sosialisasi Penyusunan Laporan Keuangan Nirlaba Berdasarkan ISAK 335 pada Rumah Sakit PKU Muhammmadiyah Makassar - Rezkiyanti, Nur Alfiah; Ulfah, Yana; Khairin, Fibriyani Nur; Asmapane, Set (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The preparation of financial statements is an obligation for every organization or enterprise, whether profit-oriented or non-profit. However, more specifically for non-profit organizations, this obligation arises as a form of transparency and accountability for the use of the funds received. Therefore, as an effort to improve the quality of financial reporting, a good understanding of the Financial Accounting Standards Interpretation (ISAK) 335, which regulates the preparation of financial statements for non-profit entities, is required by fund managers. Therefore, this socialisation activity was conducted at the Rumah Sakit Pembinaan Kesejahteraan Umat (RS PKU) Muhammadiyah Makassar, which is one of the not-for-profit oriented entities. The activity aims to enhance the hospital management's understanding of ISAK 335, provide practical guidance in preparing non-profit financial statements by accounting standards, improve transparency and accountability in hospital financial management, and prevent potential errors in financial statement presentation that could impact audits and decision-making. The results of the conducted socialisation activities are expected to contribute to the hospital's implementation of ISAK 335, which can then enhance transparency, allowing donors and stakeholders to understand how funds are used, and facilitate the audit process, as the reports become more systematic and in accordance with general accounting standards.